Are we there yet? : a case study on SLU carpark management policy - Jankulovski, Filip (SLU/Dept. of Economics, 2018)
With the technological advances that has come up since the industrial revolution our standard of living has gone up. With these advances a line of environmental and social problems has emerged. The United Nations has come up with a wide range of sustainable development gaols to help combat these problems. Swedish Agriculture of Science, SLU are in line with the goal “Climate Action” and has made changes to their environmental policies to achieve their vision of becoming climate neutral by the year 2027. One proposal to these environmental policies is to introduce a carpark management policy that would install a fee on their three main campuses Alnarp, Ultuna and Umeå and with the hope of leading their employees looking for other alternatives for workplace travel.